Urgensi tabayyun dan kualitas informasi dalam membangun komunikasi - Faisal Syarifudin (IAIN Padangsidimpuan, 2019)
This paper aims to show the urgency of tabayyun in establishing good communication and its theoretical implication. The empirical occasion in which al-Hujurat: 6 was revealed has a great relevance to the situation in the modern day where many problems result from the dissemination of information. This study of literatures demonstrates that several criteria of information quality extracted from al-Qur'an and modern theories complement each other to build a theoretical model that involves the character of iman and fasiq in the personality of communicators and communicants